Structural Characterization of Black Widow Spider Dragline Silk Proteins CRP1 and CRP4 - Mikayla Shanafelt; Taylor Rabara; Danielle MacArt; Caroline Williams; Ryan Hekman; Hyun Joo; Jerry Tsai; Craig Vierra (Molecules, 2020)
Spider dragline silk represents a biomaterial with outstanding mechanical properties, possessing high-tensile strength and toughness. In black widows at least eight different proteins have been identified as constituents of dragline silk. These represent major ampullate spidroins MaSp1, MaSp2, MaSp’, and several low-molecular weight cysteine-rich protein (CRP) family members, including CRP1, CRP2, and CRP4. Molecular modeling predicts that CRPs contain a cystine slipknot motif, but experimental evidence to support this assertion remains to be reported. To advance scientific knowledge regarding CRP function, we recombinantly expressed and purified CRP1 and CRP4 from bacteria and investigated their secondary structure using circular dichroism (CD) under different chemical and physical conditions. We demonstrate by far-UV CD spectroscopy that these proteins contain similar secondary structure, having substantial amounts of random coil conformation, followed by lower levels of beta sheet, alpha helical and beta turn structures. CRPs are thermally and pH stable; however, treatment with reagents that disrupt disulfide bonds impact their structural conformations. Cross-linking mass spectrometry (XL-MS) data also support computational models of CRP1. Taken together, the chemical and thermal stability of CRPs, the cross-linking data, coupled with the structural sensitivity to reducing agents, are experimentally consistent with the supposition CRPs are cystine slipknot proteins.